Assimilation Program Planning By The Ministry Of Law And Human Rights In Overcoming The Spread Of Covid-19 At The Corporate Institution - Nurhidayah, Isti (International Journal of Educational Research & Social Sciences, 2022)
The purpose of this study was to determine the assimilation program launched by the Ministry of Law and Human Rights in order to overcome the spread of Covid-19 in prisons so that it does not over capacity. The type of research method used is normative juridical. Based on the results of the study, it is known that if assimilation and integration continue to apply, there are at least two additional requirements, namely; The provision of assimilation and integration must involve supervisory judges and observers for their consideration and risk assessment. Furthermore, for the long term, in anticipating overcapacity in correctional institutions, immediately ratify the Draft Criminal Code which has the concept of Criminal Individualization and Criminalization which is expected to be able to provide protection and welfare for the community and still pay attention to the interests of criminal acts.